Multidimensional Analysis of Linguistic Variation in the Russian Speeches Before War in Ukraine - Bahaa-eddin Hassan (Language Value)
Linguistic variation is a trending topic to study genre analysis on the grounds of theory, methodology, and practicality. This study sets out to explore the genre analysis and text type of Russian speeches at the Munich Security Conferences MSC from 2007 to 2018 using multidimensional analysis. Through comparative Multi-dimensional (MD) analysis homogeneous and heterogeneous linguistic features are found. Data for the current research is taken from MSC websites by the selection of 13 Russian speeches allocated into the sub-categories of expository texts. For comparative MD analysis of sub-genre of the English version of the Russian speeches at MSC MAT tagger 1.3.3 findings were taken. The outcome indicates that there are high scores on D3 and D5 and low scores on D1 which suggests that the expository genre is utilized in the Russian speeches in MSC. The possible reasons for this linguistic variation are also discussed in the conclusion.